Biomechanical and psychophysiological features of qualified veteran boxers of various fighting styles - Valentyn Kozin; Maryna Omelchenko; Iryna Turchyk; Iryna Yesman (H.S. Skovoroda Kharkiv National Pedagogical University, 2022)
Purpose: to give a comparative description of the peculiarities of motor activity of boxers-veterans of different styles of fighting based on the analysis of psychophysiological and biomechanical parameters. Material and Methods: The study involved 42 qualified veteran boxers (age 45-50 years, body length - 178.67±8.26 cm, body weight - 70.96±9.38 kg). The biomechanical indicators of a direct blow in boxing were recorded using the Kinovea program, version 0.8.15, and psychophysiological indicators using the Psychodiagnostics program. As biomechanical indicators, the speed of movement of various points of the limbs and the angles in the joints were determined. As psychophysiological indicators, the speed of a simple visual-motor reaction, a reaction of choice in various testing modes was recorded. Based on these indicators, the mobility and endurance of the nervous system were determined. The reliability of differences between groups of different fighting styles was determined. Results. Tempo-style boxers differ from representatives of other fighting styles in their lower mobility of the nervous system and greater endurance for speedy and precise actions. Tempo-style boxers have the lowest values ​​of the angle in the knee joint throughout the movement (p<0.05, p<0.01) and the highest speed of movement. Play style boxers are characterized by the greatest angle in the shoulder joint at the very beginning of the movement (p<0.05, p<0.001), the highest speed of fist and shoulder movement at the very beginning of the movement (p<0.001). Power style boxers develop maximum movement speed at the end of a straight punch compared to the beginning. Power style boxers are distinguished by the smallest values ​​of the angle in the elbow joint, which is especially noticeable at the end of the movement (p<0.001). Conclusions. Psychophysiological features of boxers of different styles of fighting are reflected in the features of the technique of a direct blow. The lack of speed when tempo-style boxers are engaged in movement is supplemented and compensated by the high speed of movement. Play style boxers are characterized by high speed of movement at the very beginning of punching. Power style boxers are distinguished by the gradual development of movement speed.